Revealing the potential of ChatGPT for English language teaching: EFL preservice teachers teaching practicum experience - I Putu Indra Kusuma; Marianus Roni; Kadek Sintya Dewi; Gede Mahendrayana (Universitas Syiah Kuala, 2024)
The potential of ChatGPT as a novel Artificial Intelligence (henceforth, AI)-powered language model for language instruction, particularly for preservice teachers (henceforth, PSTs), remains unclear since earlier studies mainly provided theoretical concepts that have not yet been empirically verified. Therefore, the purpose of this study was to unleash the potential of ChatGPT for English language teaching and professional development. This qualitative study employed a phenomenological approach. The participants in this study were eight preservice English as a foreign language (henceforth, EFL) teachers at an Indonesian public university who were completing teaching practicums. Combining online and offline meetings, this study used in-depth, semi-structured interviews. Inductive thematic analysis was employed to analyze the data, and the results show that the PSTs used ChatGPT for four main purposes (innovative teaching content creation and presentation, collaborative instructional strategies, development of effective assessments, and language proficiency improvement) to improve their teaching techniques during the teaching practicums. The results also suggest that ChatGPT could provide comprehensive and relevant information. Still, at some points, it also has some drawbacks regarding the quality and accuracy of the information. Although ChatGPT has several disadvantages, the participants had a positive view of ChatGPTs value to novice teachers professional growth. This study offers three implications for improving English language teaching and preservice teacher professional development.